2018
DOI: 10.1634/theoncologist.2017-0271
|View full text |Cite
|
Sign up to set email alerts
|

Cervical Cancer in Ethiopia: The Effect of Adherence to Radiotherapy on Survival

Abstract: This study presents the effect of adherence on survival of 788 patients with cervical cancer receiving external beam radiotherapy without brachytherapy in Ethiopia. Discontinuation of planned radiotherapy according to local guidelines considerably reduced survival for all International Federation of Gynecology and Obstetrics (FIGO) stages treated (hazard ratios were 1.3, 3.1, and 7.3 for FIGO stages IIA-IIIA and IIIB-IVA and the palliative approach, respectively). Early toxicity (5% grade 3) should be treated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
32
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 32 publications
(37 citation statements)
references
References 38 publications
4
32
1
Order By: Relevance
“…The current result is in agreement with study conducted on the effect of adherence of radiation therapy for one-year survival in Ethiopia which was 96% for radical therapy and 87% for those who took none radical radiation therapy [21]. This may be due to the similarity of study setting, treatment modalities and roughly the same sample sizes of study participants.…”
Section: Discussionsupporting
confidence: 91%
“…The current result is in agreement with study conducted on the effect of adherence of radiation therapy for one-year survival in Ethiopia which was 96% for radical therapy and 87% for those who took none radical radiation therapy [21]. This may be due to the similarity of study setting, treatment modalities and roughly the same sample sizes of study participants.…”
Section: Discussionsupporting
confidence: 91%
“…27 To our knowledge, there are no other published reported rates of acute RT toxicity in head and neck cancer in sub-Saharan Africa. Moelle et al 28 reported grade 3 early toxicity in 5% of patients with cervical cancer who received curative RT in the same center in Ethiopia, which was a considerably higher rate than in this study. This is at least partially a result of the addition of brachytherapy during our study period, which alleviates the need for an external-beam boost, causing higher toxicity to the surrounding tissue.…”
Section: Discussioncontrasting
confidence: 66%
“…We conducted a retrospective cohort study among cervical cancer patients who registered at Tikur Anbessa Specialized Hospital (TASH), Addis Ababa, Ethiopia between September 2008 and September 2012 as described earlier [6, 14, 15]. TASH is the largest hospital in Ethiopia and the only hospital in the country currently offering radiotherapy – thus, people from all parts of the country were referred there for therapy.…”
Section: Methodsmentioning
confidence: 99%